PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER (NHT) DAN GAYA BELAJAR TERHADAP KETERAMPILAN SOSIAL PADA SISWA SMAN 3 SIGI - Asrida, Asrida (Katalogis, 2016)
This research aims: (1) to find out the effect of cooperative learning model Numbered Head Together (NHT) type on social skill of students at SMAN 3 Sigi; (2) to find out the effect of learning style on social skill of the students at SMAN 3 Sigi; and (3) to find out the effect of cooperative learning Numbered Head Together type and learning style toward social skill of the students at SMAN 3 Sigi. The sample was 32 students of class XI Social 2. They were selected through purposive sampling that functioned to take some people based on certain criteria based on the research objective. This was a correlational descriptive research with multiple linear regression analysis technique. The results indicate that variable of cooperative learning model Numbered Head Together type (X1) have effect toward social skill of students at SMAN 3 Sigi with tcounted value of 2.159 > ttable 2.045; and variable of learning style have effect toward social skill of students at SMAN 3 Sigi with tcounted value of 2.050 > ttable 2.045. Moreover, variable of cooperative learning model Numbered Head Together type (X1) and learning style (X2) simultaneously have effect toward social skill of students at SMAN 3 Sigi with Ftcounted value of 27.234 > Ftable 1.84.Â